Bugis Village Perceptions Toward Tialo Language Maintenance - Anisa Anisa; Rizky Anugrah Putra (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2025)
This study aims to describe the perceptions of the Bugis Village community regarding the maintenance of the Tialo language and to examine the role of the government and relevant stakeholders in its preservation efforts. As one of the regional languages in Central Sulawesi, Tialo faces a decline in usage driven by the dominance of the Bahasa Indonesia, and low interest among the younger generation. This study employs a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, questionnaires, and documentation. The sample consists of 250 respondents selected through a non-probability sampling technique. The findings indicate that while the community holds a positive perception regarding the importance of maintaining the Tialo language, its usage remains predominantly confined to the older generation. Meanwhile, the government's role in supporting language preservation is still considered low.